Revisiting the role of within-compound associations in cue-interaction phenomena. - Luque-Ruiz, David; Flores, Amanda; Vadillo, Miguel Ángel (Springer, 2012)
Although it is thought that within-compound associations are necessary for the occurrence of both backward blocking and unovershadowing, it is not known whether this variable plays a similar role in mediating the two phenomena. Similarly, the roles of within-compound associations in forward blocking and in reduced overshadowing have not been tested independently. The present experiments evaluated how the strength of within-compound associations affects backward blocking, unovershadowing, forward blocking and reduced overshadowing. Using an allergy task, the strength of withincompound associations was varied by taking advantage of the participants’ prior knowledge of common and uncommon food pairings. Backward blocking and unovershadowing effects were only present when highly memorable compound cues were used. Moreover, the magnitudes of both retrospective revaluation effects were affected by the strength of within-compound associations. Forward blocking and reduced overshadowing effects were independent of within-compound associations. These results have important theoretical implications for causal learning research.
https://openpolicyfinder.jisc.ac.uk/id/publication/28603
Keywords: Conducta - Modificación; Backward blocking